Validation of the Flourishing Scale and Scale of Positive and Negative Experience in Portugal - Junça Silva, A.; Caetano, A. (Social Indicators Research, 2013)
The Flourishing Scale (FS) and the Scale of Positive and Negative Experience (SPANE) created by Diener et al. (Soc Indic Res 97:143–156, 2010) are instruments that assess psychological flourishing and feelings (positive and negative, and the difference between the two). In this study, the psychometric properties of both scales were explored by using two Portuguese samples (I: n = 734; II: n = 194). Reliability analysis and a multi-group confirmatory factorial analysis (MCFA) of both scales were performed. To examine the validity of FS and SPANE we analyzed their correlations with other well-being and happiness measures. Results showed that the Portuguese versions of both scales have good psychometric properties, and they also showed convergent validity. Results also demonstrated the unidimensional structure of the FS and a two-factor solution for the SPANE. The multi-group CFA of both scales evidenced an invariant structure. Both Portuguese versions of the scales behave consistently with the original and may be used in future studies of well-being.